"I know exactly what I'm going into": recommendations for pre‐nursing experience from an evaluation of a pre‐nursing scholarship in rural Scotland. Issue 3 (19th September 2015) - Smith, Annetta; Beattie, Michelle; Kyle, Richard G.
Abstract: Aim: To develop a model of pre‐nursing experience from evaluation of a pre‐nursing scholarship for school pupils in Scotland. Design: Action research study. Methods: School pupils ( n  = 42) completed questionnaire surveys and participated in anecdote circles. Student nurses acting as pupil 'buddies' ( n  = 33) participated in focus groups. Descriptive quantitative data and thematic analyses of qualitative data were integrated across cohorts and campuses. Results: Ten recommended components of a model of pre‐nursing experience were identified: educational experience of: (1) face‐to‐face on‐campus teaching; (2) hands‐on clinical skills sessions; and (3) andragogy, practice exposure to (4) nursing language; (5) nurses' emotional labour; (6) patients' stories; (7) pupils socializing with buddies; (8) buddies planning placement activities; and (9) supporting pupils during placements. Academic attainment was not a central component of the model due to pupils' need to (10) prioritize examined work for further/higher education entry.